Axillary arch muscle- a case report - Kanika Sachdeva; Monika Lalit; Anupama Mahajan; Poonam Delmotra (Wolters Kluwer Medknow Publications, 2015)
Anomalous muscles donot usually cause symptoms but are of academic interest. Axillary arch is a variable muscular slip encountered in axilla. Purpose of the present study was to report a rare case of axillary arch muscle. Knowledge of this muscle variation and the possibility of finding it during axillary procedures are crucial for lymph node staging, lymphaedenectomy and for differential diagnosis in compressive pathologies of axillary vessels and brachial plexus. During routine dissection of left axilla in a 60-year old male cadaver, an anomalous muscular slip was encountered. The slip was extending between latissimus dorsi muscle to coracoid process, deltoid muscle, fascia covering biceps and coracobrachialis and was confirmed as axillary arch muscle. The embryological basis, genetics and clinical implications have been discussed. This rare variation will be of interest not only to anatomists but also for clinicians and surgeons dealing with this area.